Strategi Pengembangan Destinasi Wisata Kabupaten Jember - Achmad Yanu Alif Fianto; Rudi Santoso (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
This study aims to analyze the strategy for developing the potential of tourism places in Jember Regency, East Java. This study focuses on activities to analyze strategies that can be used by the Jember Regency Government so that it can focus on the main strategy, namely tourism development in Jember Regency, East Java. The survey subjects were all tourists and residents around tourism sites in Jember Regency who participated in the development of tourism sites in Jember Regency, and the survey sample was obtained from directly. Data collection uses previous research review techniques and theoretical concepts that underlie tourism strategies, surveys, and in-depth interviews. This study uses data analysis techniques in the form of qualitative descriptive analysis. The results and findings in this study show that tourism places in Jember Regency have the potential of a very worthy area to get more attention in terms of sustainable tourism development.